Blue rhythm fantasy : big band jazz arranging in the swing era - Wriggle, John (Music in American life., 2016)
"Behind the iconic jazz orchestras, vocalists, and stage productions of the Swing Era lay the talents of popular music's forgotten stars: the arrangers. John Wriggle takes you behind the scenes of New York City's vibrant entertainment industry of the 1930 and 1940s to uncover the lives and work of jazz arrangers, both black and white, who left an indelible mark on American music and culture. [This book] traces the ... career of arranger Chappie Willet - a collaborator of Louis Armstrong, Cab Calloway, Duke Ellington, Gene Krupa and many others - to revisit legendary Swing Era venues and performers from Harlem and Times Square. Wriggle's ... music analyses of big band arranging techniques explore representations of cultural modernism, discourses on art and commercialism, conceptions of race and cultural identity, music industry marketing strategies, and stage entertainment variety genres."--Back cover